2012
DOI: 10.1002/ana.23626
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microglial N‐methyl‐D‐aspartate receptors triggers inflammation and neuronal cell death in the developing and mature brain

Abstract: Our findings link inflammation and excitotoxicity in a potential vicious circle and indicate that an activation of the microglial NMDARs plays a pivotal role in neuronal cell death in the perinatal and adult brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(121 citation statements)
references
References 62 publications
3
117
1
Order By: Relevance
“…The AMPA type of glutamate receptor has been shown to be present in cultured microglia (145,287), along with metabotropic glutamate receptors: mGluR5 (group I), mGluR2, mGluR3 (group II) and mGluR4, mGluR6, and mGluR8 (group III) (38, 238,259,399,400,401). There is evidence for the expression NMDA receptors on microglia also in the intact brain, although no in situ electrophysiological data have been given (181). Microglia in culture express metabotropic GABA B receptors (205), whereas microglial responses to GABA A receptor activation (284) are thought to be due to indirect effects (65).…”
Section: B Microglia Express Neurotransmitter Receptorsmentioning
confidence: 99%
“…The AMPA type of glutamate receptor has been shown to be present in cultured microglia (145,287), along with metabotropic glutamate receptors: mGluR5 (group I), mGluR2, mGluR3 (group II) and mGluR4, mGluR6, and mGluR8 (group III) (38, 238,259,399,400,401). There is evidence for the expression NMDA receptors on microglia also in the intact brain, although no in situ electrophysiological data have been given (181). Microglia in culture express metabotropic GABA B receptors (205), whereas microglial responses to GABA A receptor activation (284) are thought to be due to indirect effects (65).…”
Section: B Microglia Express Neurotransmitter Receptorsmentioning
confidence: 99%
“…Recent studies also show that microglia express NMDA receptors, and it is possible that these cells may react to high levels of extracellular glutamate, resulting in propagation of neuronal damage [229]. NMDA receptor stimulation triggers microglia activation and secretion of factors that induce cell death of cortical neurons, and in turn, damaged neurons activate microglial NMDA receptors to aggravate neurologic disease [230].…”
Section: Microgliamentioning
confidence: 99%
“…A recent study even showed that ramified microglia plays an active protective role against NMDA induced excitotoxicity (Vinet et al, 2012). On the other hand, another study showed that microglia expresses functional NMDA receptors that upon activation may trigger secretion of factors leading to neuronal death (Kaindl et al, 2012). However, we were not able to distinguish their phenotype and role during NMDA induced neurodegeneration with immunohistochemistry.…”
Section: Neurodegeneration Was Accompanied With Progressive Neuroinflmentioning
confidence: 63%